Frequency of High Cup to Disc Ratio amongst Healthy Young Population of Central Punjab Province of Pakistan - Parveen, Shagufta; Muzaffar, Waqar; Saeed, Muhammad Kamran; Babar, Zaheer Uddin; Tanveer, Hira (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency of high cup-to-disc ratio amongst the healthy young population of the Central Punjab province of Pakistan. Study Design: Cross-sectional study. Place and Duration of Study: Department of Eye, Combined Military Hospital Lahore, from Jun 2022 to Feb 2023. Methodology: One hundred fifteen candidates who presented for medical fitness examinations were enrolled; they all belonged to the Central Punjab province of Pakistan. All the participants underwent thorough ocular examination, including visual acuity testing, slit lamp bio-microscopy, fundoscopy and tonometry. Candidates with a cup-to-disc ratio >0.6 were further investigated to rule out glaucoma using pachymetry, visual field (VF) testing and spectral-domain optical coherence tomography. Results: The mean age of participants of the study was 18.97±2.60 years. There were 72(62.6%) males and 43(37.4%) females.The mean intraocular pressure was 13.08±2.40 mmHg. The mean cup-to-disc ratio was calculated to be 0.34±0.11. It was found that 7 out of 115(6.1%) participants have a cup-to-disc ratio of more than 0.6, whereas the remaining 108(93.9%) participants had less than 0.6 cup-to-disc ratio. Conclusion: The screened population revealed a high cup-to-disc ratio in 6.1% of the candidates.